Coding and non-coding variants in the SHOX2 gene in patients with early-onset atrial fibrillation - Hoffmann, Sandra; Clauss, Sebastian; Berger, Ina Maria; Weiß, Birgit; Montalbano, Antonino; Röth, Ralph; Bucher, Madeline; Klier, Ina; Wakili, Reza; Seitz, Hervé; Schulze-Bahr, Eric; Katus, Hugo; et al. (Basic research in cardiology, 2016)
Atrial fibrillation (AF) is the most prevalent cardiac arrhythmia with a strong genetic component. Molecular pathways involving the homeodomain transcription factor Shox2 control the development and function of the cardiac conduction system in mouse and zebrafish. Here we report the analysis of human SHOX2 as a potential susceptibility gene for early-onset AF. To identify causal variants and define the underlying mechanisms, results from 378 patients with early-onset AF before the age of 60 years were analyzed and compared to 1870 controls or reference datasets. We identified two missense mutations (p.G81E, p.H283Q), that were predicted as damaging. Transactivation studies using SHOX2 targets and phenotypic rescue experiments in zebrafish demonstrated that the p.H283Q mutation severely affects SHOX2 pacemaker function. We also demonstrate an association between a 3′UTR variant c.*28T>C of SHOX2 and AF (p = 0.00515). Patients carrying this variant present significantly longer PR intervals. Mechanistically, this variant creates a functional binding site for hsa-miR-92b-5p. Circulating hsa-miR-92b-5p plasma levels were significantly altered in AF patients carrying the 3′UTR variant (p = 0.0095). Finally, we demonstrate significantly reduced SHOX2 expression levels in right atrial appendages of AF patients compared to patients with sinus rhythm. Together, these results suggest a genetic contribution of SHOX2 in early-onset AF.
Gesehen am 21.02.2020